2018
DOI: 10.1097/pr9.0000000000000667
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational examination of pain and posttraumatic stress disorder symptoms among youth with chronic pain and their parents

Abstract: Introduction:Posttraumatic stress disorder (PTSD) symptoms are prevalent among youth with chronic pain, and associated with poorer pain outcomes and health-related quality of life (HRQoL). Conceptual models suggest that parent factors, including parents' own chronic pain, may be linked to higher co-occurring pain and PTSD symptoms and lower HRQoL in children. However, this has not been empirically examined.Objectives:The aim of this study was to examine the relationship between parental chronic pain and (1) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 45 publications
(57 reference statements)
3
37
0
Order By: Relevance
“…This finding is consistent with previous ACE research showing unique associations between physical neglect and chronic pain 52 , 57 and may reflect the high rates of chronic pain observed in parents of youth with chronic pain. 10 , 53 The community-based sample comprised adults attending primary care clinics for various issues and was thus treatment-seeking. Given associations between ACEs and poor health, treatment-seeking adults may be more likely to report ACEs than adults not attending medical appointments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with previous ACE research showing unique associations between physical neglect and chronic pain 52 , 57 and may reflect the high rates of chronic pain observed in parents of youth with chronic pain. 10 , 53 The community-based sample comprised adults attending primary care clinics for various issues and was thus treatment-seeking. Given associations between ACEs and poor health, treatment-seeking adults may be more likely to report ACEs than adults not attending medical appointments.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of parenting behaviors on the functioning of youth with chronic pain is well-established, 16 and research suggests parents' mental health and physical health are also related to children's chronic pain outcomes. 10 , 12 , 19 , 26 , 32 , 42 , 47 However, adverse childhood experiences (ACEs) among parents of youth with chronic pain have not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is important to keep in mind that many patients who present with chronic pain also report symptoms of anxiety or depression, and have a history of psychological trauma or adverse childhood experiences [ 86 , 87 , 88 , 89 ]. Symptoms that are associated with posttraumatic stress disorder have a high prevalence in youth with chronic pain – and in their parents [ 90 ]. Hence, having an interdisciplinary team of professionals who share a common understanding of pediatric chronic pain and is familiar with psychiatric disorders and diagnostics is crucial to provide the best care possible for this patient group that often presents with a range of symptoms and comorbidities.…”
Section: What Is Important To Keep In Mind In the Clinical Settingmentioning
confidence: 99%
“…Among treatment seeking families of youth with chronic pain, recent literature has identified that 50% of parents of youth with chronic pain also report having chronic pain themselves [56]. In addition to potential increased risk for chronic pain conferred via genetic factors, a parent’s personal experience of coping with their own chronic pain can have powerful implications for the support that they are able to provide their child to effectively self-manage their own pain.…”
Section: Introductionmentioning
confidence: 99%